The general characteristics of names in the Armenian-Kipchak monuments - Nurila Shaymerdinova, Bibigul Zhiyembay, (Opción, 2019)
The article analyzes the category of names of medieval Armenian-Kipchak languages, which are found in the language of the monuments of Tore bitigi and Kypchak grammar via methods of scientific characterization, historical-comparative analysis, counting, differentiation of the necessary data, generalization, traditional systematization, semantic analysis. As a result, In the Kipchak era it is possible to observe that in the memo language the active, numerical, predictable, partial names of the numerals are actively used. In conclusion, the form and content of the words were investigated in terms of Runic Monuments and Modern Turkic languages.